PENGARUH RETURN ON ASSET, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP AUDIT DELAY - Fina Rahmawati; Nurhayati (Publika Citra Media, 2026)
The purpose of this study is to identify the effect of Return on Assets, Leverage, and Company Size on Audit Delay, both simultaneously and partially. The selected population consists of companies in the Transportation and Logistics Sector listed on the Indonesia Stock Exchange (IDX) for the period 2020-2024. Sampling was conducted using a purposive sampling method in accordance with predetermined criteria, involving 10 companies. Return on Assets, Leverage, and Company Size each have a significant effect on Audit Delay simultaneously. Return on Assets partially has no impact on Audit Delay. Leverage partially has an effect on Audit Delay. Company size partially does not affect Audit Delay.